Serum glial cell line-derived neurotrophic factor (GDNF) a potential biomarker of executive function in Parkinson’s disease - Tong, Shu-Yan; Wang, Rui-Wen; Li, Qian; Liu, Yi; Yao, Xiao-Yan; Geng, De-Qin; Gao, Dian-Shuai; Ren, Chao (Frontiers in Neuroscience, 2023)
Objective Executive dysfunction is the most prominent feature of cognitive dysfunction in Parkinson’s disease (PD). Evidence shows that the impairment of executive function (EF) is mainly related to the degeneration of frontal-striatal dopamine pathway. Glial cell line-derived neurotrophic factor (GDNF), as the strongest protective neurotrophic factor for dopaminergic neurons (DANs), may be related to EF. This study mainly explored the correlation between serum GDNF concentration and EF in PD. Methods This study recruited 45 healthy volunteers (health control, HC) and 105 PD patients, including 44 with mild cognitive impairment (PD-MCI), 20 with dementia (PD-D), and 20 with normal cognitive function (PD-N). Neuropsychological tests were performed to evaluate EF (working memory, inhibition control and cognitive flexibility), attention, language, memory and visuospatial function. All subjects were tested for serum GDNF and homovanillic acid (HVA) levels by ELISA and LC-ESI-MS/MS, respectively. Results PD-MCI patients showed impairments in the tail making test trial A (TMT-A), tail making test trial B (TMT-B), clock drawing test (CDT) and semantic fluency test (SFT), whereas PD-D patients performed worse in most EF tests. With the deterioration of cognitive function, the concentration of serum GDNF and HVA in PD patients decreased. In the PD group, the serum GDNF and HVA levels were negatively correlated with TMT-A and TMT-B scores, positively correlated with auditory verbal learning test (AVLT-H) and SFT scores. Serum HVA levels showed a positively correlation with DST scores. Stepwise linear regression analysis suggested that serum GDNF and HVA concentrations and UPDRS-III were the influence factors of TMT-A and TMT-B performances in PD patients. Conclusion The decrease of serum GDNF concentration in PD patients was associated with impaired inhibition control, cognitive flexibility, attention and memory. Serum GDNF and HVA levels were the influence factors of inhibition control, cognitive flexibility and attention performances in, and might synergistically participate in the occurrence and development of executive dysfunction.